Analytical diffusion model for flood routing with downstream effect - Manandhar, Shyam K.; Tawatchai Tingsanchali; Suphat Vongvisessomjai; Gupta, Ashim Das; The Royal Netherlands Government (Bangkok : Asian Institute of Technology, 1982)
An analytical diffusion model for flood routing which can take into account, the backwater effect, has been developed. The results obtained by applying the model to a hypothetical rectangular channel checked very well with those obtained by using finite difference model with implicit scheme based on the complete Saint-Venant equations for unsteady flow in open channels. The computation time for this model is comparatively less and the model can be used even without computer facility. The model was extended to include the lateral inflow also and the results obtained were found also to be quite satisfactory.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1982
Keywords: Diffusion in hydrology